In Vitro antifungal activity of ethanol extracts from Cnidoscolus urens L. in controlling Colletotrichum spp. in Lycopersicum esculentum: a sustainable agricultural perspective - Carrillo, María Fernanda; Mora-Estupiñan, Daniela Alejandra; Ortiz-Rojas, Luz Yineth; Chaves-Bedoya, Giovanni (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Anthracnose, caused by the pathogenic fungi Colletotrichum spp., poses a significant threat to table tomato (Lycopersicum esculentum) cultivation. This study delves into the potential of plant extracts from Cnidoscolus urens L. as an alternative biocontrol strategy to combat this disease. Rich in secondary metabolites like terpenes, which are instrumental in plant defense, these extracts also comprise esters and fatty acids. Although the latter are not classified as secondary metabolites, they contribute significantly to the plant's biochemical makeup. Our objective was to gauge the in vitro inhibitory efficacy of ethanolic extracts derived from the leaves and stems of Cnidoscolus urens L. against Colletotrichum spp. To achieve this, an agar dilution method with varying extract concentrations was employed. The results showed that concentrations ranging from treatment 3 to treatment 8 effectively inhibited fungal mycelial growth. Interestingly, the extracts' origin, whether from leaves or stems, did not show any significant differential impact on their inhibitory activity. These insights emphasize the consistent effect of Cnidoscolus urens L. extracts in stalling Colletotrichum spp. growth, underscoring their potential as biological antifungal agents in agriculture. Given the pronounced in vitro effectiveness of both leaf and stem extracts, they beckon further exploration as part of sustainable agricultural strategies to combat prominent diseases like anthracnose.